Assessing off-site readiness in construction organisations: cases from India. Issue 2 (9th July 2021) - Bendi, Deepthi; Rana, Muhammad Qasim; Arif, Mohammed; Lamb, Steve Michael; Sawhney, Anil; Kaushik, Amit Kant
Abstract : Purpose: This paper aims to present factors affecting the Indian construction organisations in adopting off-site construction (OSC) methods. Design/methodology/approach: An existing readiness maturity model has been used to assess three large organisations in different parts of India. A case study methodology has been adopted in this paper to highlight critical issues in OSC adoption in India. Findings: This paper presents three case studies and concludes the Indian construction sectors readiness to adopt the OSC methods. Through the case studies, different issues related to the adoption of OSC have been identified and highlighted for the Indian construction sector. Although the three companies are large, there are several small- and medium-sized enterprises (SME) operating in India's construction sector, and future research shall be needed to review these SMEs. Research limitations/implications: This research study is broadly focused on developing and assessing an OSC readiness framework for Indian construction organisations. The research scope and the population for data collection are limited to large construction organisations in India only. Practical implications: The proposed OSC readiness maturity model guides construction practitioners in India through a structured process to assess their OSC readiness in the market. This assessment enables them to evaluate and benchmark their processes through the strategic and operational phases. This research will add to the existing knowledge of OSC in India by mapping issues relevant to India's construction industry. The research has provided background on the status of OSC, the drivers and barriers affecting the implementation of OSC techniques in the Indian construction industry. Originality/value: Through the three case studies, several factors related to the implementation of OSC methods have been identified and highlighted within the Indian construction sector. Although the model has been applied to the Indian construction sector, it can easily be modified to fit into other areas and similar dynamics and business conditions.